A descriptive review on the real-world impact of Moderna, Inc. COVID-19 vaccines - Mary Bausch-Jurken; Rachel S Dawson; Francesca Ceddia; Veronica Urdaneta; Morgan A Marks; Yohei Doi (Taylor & Francis Group, 2024)
Introduction Since the original COVID-19 vaccines were developed, abundant clinical trial and real-world evidence evaluating the efficacy, effectiveness, and safety of COVID-19 vaccines has been collected. Knowledge of the relative benefits and risks of COVID-19 vaccines is essential for building trust within target populations, ensuring they remain effectively and safely protected against an enduring infectious threat.Areas covered This descriptive review discusses the benefits and risks associated with marketed Moderna, Inc. mRNA-based COVID-19 vaccines, focusing on their real-world effectiveness and safety profiles in various age groups. Adverse events of interest and potential benefits of vaccination are reviewed, including reduced risk for severe COVID-19 and long-term health outcomes, reduced economic and societal costs, and reduced risk for SARS-CoV-2 transmission.Expert opinion Post-marketing safety and real-world data for Moderna, Inc. COVID-19 mRNA vaccines strongly support a positive benefit - risk profile favoring vaccination across all age groups. Although COVID-19 is no longer considered a global health pandemic, health risks associated with SARS-CoV-2 infection remain high. Concerted efforts are required to engage communities and maintain protection through vaccination. Continued surveillance of emerging variants and monitoring of vaccine safety and effectiveness are crucial for ensuring sustained protection against SARS-CoV-2.